Narrating the Anthropocene in the Delta under Authoritarian Development: A Corpus-Driven Analysis of Eco-political Transformation Discourse - Shaikh, Hasan; Akter, Lamiya (Abjad Journal of Humanities & Education, 2025)
In the era of the Anthropocene, where human activity increasingly defines planetary change, this study examines how the Bangladesh Delta Plan 2100, the state’s flagship strategy for climate resilience and development, constructs and circulates eco-political narratives through a corpus of 1803169 tokens drawn from official government reports published between 2018 and 2019. Drawing on corpus-driven methods, including network, concordance, and n-gram analysis, the paper interrogates the textual architecture to uncover how the state mobilizes language to legitimize particular forms of governance. The findings show the dominance of managerial and technocratic framings in its eco-political discourse. Networks link governance and efficiency with ecological keywords, recasting climate threats as solvable through centralized implementation and expert consensus. Concordance patterns expose spatial hierarchies: drought-prone regions are framed as peripheral zones needing intervention, while “urban and rural” pairings suggest inclusivity yet obscure uneven resource distribution. These textual strategies reinforce anticipatory development logics that privilege national modernization. N-gram analysis further shows how economic rationalities permeate sustainability language, signaling a shift toward neoliberal governance. Water resilience is reframed as a cost-recovery issue, not a collective right, revealing how Anthropocene vulnerabilities are mobilized to justify market-based solutions and entrench unequal access to protection and resources. Moreover, this study situates Bangladesh’s delta discourse within global debates on authoritarian development, eco-political transformation, and post-political environmentalism, showing how crisis rhetoric legitimizes centralized, market-driven governance. While limited to official texts, the research calls for future works incorporating grassroots and civil society narratives to foreground more pluralistic, climate-just, and democratically inclusive pathways toward sustainability in the Anthropocene.